BIM-based Code Checking for Construction Health and Safety. (2017) - Getuli, Vito; Ventura, Silvia Mastrolembo; Capone, Pietro; Ciribini, Angelo L.C.
Abstract: Rule-based Code Checking validates the design phase comparing Building Information Models against current codes and regulations translated into parametric rules. The proposed paper fits into a wider project for implementing design verification and validation within a BIM environment. The design of construction site layouts and safety plans is an essential part of an effective integrated process but it is traditionally carried out by means of error-prone and inefficient manual observation and, moreover, building designers and health and safety (H&S) coordinators still lack a collaborative working approach. The digitization of the construction site allows virtual inspections and information-based analysis of construction phases. Moreover, interoperable BIM tools allow the semi-automatic review of design compliance against normative texts, improving accuracy and reliability of the validation process. The research project aims to define an H&S BIM-based design and validation workflow, specifying the minimum level of requirements and mandatory informative content for the submission of construction site layouts and safety plans. The paper is focused on the translation into a parametric rule-set of the Italian construction sites' H&S normative text (D.Lgs. 81/2008). A semantic analysis was used in order to translate it into computable parameters to be implemented into checking rules. Object tables have been created for each construction site element regulated by the D.Lgs. 81/2008. Based on those tables, meant as guideline for the design phase, a BIM library for the construction site has been created and a model checking tool has been used for creating rules to check and validate BIM objects and mutual relations. The customized rule-set includes legal references and information requirements specifications. Such an approach aims at including the design of construction safety plans within digital